2020
DOI: 10.1186/s12887-020-02278-4
|View full text |Cite
|
Sign up to set email alerts
|

Admission platelet count and indices as predictors of outcome in children with severe Sepsis: a prospective hospital-based study

Abstract: Background: Sepsis is still one of the main causes of infants and children mortality especially in developing, economically challenged countries with limited resources. Our objective in this study was to determine, the prognostic value of platelet count, mean platelet volume (MPV), platelet distribution width (PDW) and plateletcrit (PCT) in critically ill infants and children with severe sepsis, as they are readily available biomarkers, that can guide clinicians during managing of severe sepsis. Methods: Sixty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 31 publications
8
22
0
Order By: Relevance
“…34,35 Further researches showed that RDW, PDW, and RPR were significantly associated with the prognosis of many diseases, such as cancer, sepsis, and cardiovascular disease. [36][37][38][39] However, there are few reports about the relationship between Nevertheless, some limitations of our study must be considered. First, the soluble interleukin-2 receptor detection was unavailable in our hospital.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…34,35 Further researches showed that RDW, PDW, and RPR were significantly associated with the prognosis of many diseases, such as cancer, sepsis, and cardiovascular disease. [36][37][38][39] However, there are few reports about the relationship between Nevertheless, some limitations of our study must be considered. First, the soluble interleukin-2 receptor detection was unavailable in our hospital.…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, red blood cell distribution width and platelet ratio (RPR) have been reported as a useful parameter describing the systemic inflammatory response by a large number of studies 34,35 . Further researches showed that RDW, PDW, and RPR were significantly associated with the prognosis of many diseases, such as cancer, sepsis, and cardiovascular disease 36–39 . However, there are few reports about the relationship between HLH and RDW, PDW, and RPR.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet count and MPV have been evaluated as prognostic markers in sepsis and septic shock. 9,17 Thrombocytopenia, on the other hand, seems to be independently associated with increased mortality in severe sepsis. Choi et al showed that thrombocytopenia in children with sepsis had an AUC of 0.79 (95% CI: 0.69-0.90).…”
Section: Discussionmentioning
confidence: 99%
“…6 Platelet volume indices are biomarkers for platelet activation and are associated with systemic inflammation 7 and have been used as inflammatory and prognostic markers in various pathologies. 8,9 These platelet volume indices, such as mean platelet volume (MPV), plateletcrit, and platelet distribution width, can often be rapidly measured by complete blood cell (CBC) count analyzers. 10 Platelet mass index (PMI) is the product of platelet count and MPV.…”
Section: Introductionmentioning
confidence: 99%
“…Platelets with increased number and size of pseudopodia differ in size, which affects PDW which increases in sepsis [24]. Sayed [25] in a study on admission platelet indices showed PDW was higher in non-survivors of sepsis but not significant, rather plateletcrit (PCT) and MPV/PCT ratio were significantly associated with mortality. Similar findings were also reported by Golwala [26].…”
Section: Discussionmentioning
confidence: 99%